Synergetic effects of network interconnections in the conditions of virtual reality - Kraus Kateryna; Kraus Nataliia; Shtepa Olena (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: The disclosure of the content of the synergetic effect, as a result of network interactions of development institutions in a new economic virtual reality, and the presentation of the general characteristics of their relationships through knowledge of the functioning of clusters, which in the XXI century occurs during the digitalization of the economy, resulting in digital products/services and various platforms. METHODOLOGY: On the basis of dialectical, systemic and matrix methods and using the institutional-network approach, the characteristic features of network interactions of cluster formations in the conditions of virtual reality are studied, which are becoming the norm today, a good quality and effective rule for the practical implementation of various sectors of the economy in the course of digitalization of the economy. The method of comparison is used in terms of conditions for the formation of an innovation-digital cluster from the standpoint of the theory of institutionalism. FINDINGS: Network cooperation in the conditions of virtual reality demonstrates synergetic effects through new forms of qualitative accumulation and an increase of new knowledge, which occur through their network replication (division), and innovative growth is the result of the formation in the economy and society of a new, network model of coordination of connections, network cooperation of new quality, constantly adjusted by digital tools. The synergistic effect of networking creates a new phenomenon of growing marginal utility and growing marginal productivity from innovative glocalization and digital globalization. The greater the scale of innovation and digital activities is in the conditions of virtual reality, the greater the efficiency is of the use of additional resources. The effect of scale is especially pronounced within the network, which uses the standards produced and tested by it. IMPLICATIONS FOR THEORY AND PRACTICE: It is proved that the synergetic approach used in the formation and development of innovation-digital clusters is considered through the prism of the relationship “subject – subjective relationship of innovation-active organizations and digital enterprises.” In addition, in our case, this effect lies in the plane of restructuring the “old” development institutions in the “new”, under the influence of the relevant institutional and legal basis, systemic and comprehensive modernization and diversification of all sectors of production, improvement of the innovation and investment situation, construction of effective innovation and digital virtual-real infrastructure of the European standard, implementation of clustering of the economy using the opportunities of network cooperation.. ORIGINALITY AND VALUE: The content of a virtual slice of network interaction of cluster formations in the conditions of virtual reality offered by the authors is revealed; the authors’ vision of its structural elements is given, as from a digital network augmented and virtual socio-economic reality; the taxonomy and categorization of terminology with the help of which it is possible to reveal the formation of network cooperation in the conditions of virtual reality and its further development are investigated; on the basis of the conducted deep theoretical and methodological analysis and the presentation of a retrospective of innovation and digital changes, a step-by-step transformation of cluster formations is shown. The basis of network economy is network institutions, entities, organizations, in addition, it forms an environment in which any business entity or individual, which, no matter where it is in the economic system, has been able to communicate easily and at minimal cost with any other company or individual about working together, trading issues, or know-how, or just for fun in the conditions of the new virtual reality.